Assessing the Effectiveness of Pharma Business by Optimum Resources Management - Gowtham, Maddipati (Digital Repository of Theses, 2025)
Pharmaceutical companies operate in an environment characterized by swift technological advancements and intense market rivalry, playing a key role in meeting critical healthcare challenges. However, with this innovation comes the challenge of managing resources effectively while maintaining cost efficiency, regulatory compliance, and sustainability concerns. This research critically examines these obstacles and formulates actionable solutions to address them. It further delineates implementation barriers and advances industry-aligned best practices derived from scholarly evidence and real-world applications. The research adopts a mixed-methods approach, combining a comprehensive literature review, surveys with industry experts, and quantitative data analysis to provide holistic insights into the subject matter. The findings of this research will contribute to the development of best practices and strategies in pharmaceutical operations, offer actionable recommendations for pharmaceutical companies, and contribute to the advancement of optimized resource management practices in the industry.